Tersilochinae (Hymenoptera: Ichneumonidae) of Papua New Guinea: genera Allophrys Förster and Probles Förster - Khalaim, Andrey I.; Villemant, Claire (Zootaxa, 2019)
Seven species of the genus Allophrys Förster, A. cracentis sp. nov., A. daklaka Khalaim, A. madanga sp. nov., A. miklouhomaclayi sp. nov., A. occipitata Khalaim, A. parvidentata sp. nov. and A. valorosa sp. nov., and one species of Probles Förster, P. (Euporizon) papuaensis sp. nov., have been discovered from Papua New Guinea. This is the first record of these genera, as well as the subfamily Tersilochinae, from this country. An identification key to seven species of Allophrys occurring in Papua New Guinea is provided.